Play ball! eaudiobook - Dean, James (My First I Can Read: Pete the Cat., 2013)
New York Times bestselling author and artist James Dean takes readers along for a fun, groovy adventure with Pete the Cat! Pete the Cat is ready to play baseball! Pete's team, the Rocks, is playing the Rolls. But when the game doesn't go Pete's way, what will Pete do? Pete the Cat: Play Ball! is a My First I Can Read book, which means it's perfect for shared reading with a child.